Secretion and functional display of fusion proteins through the curli biogenesis pathway. Issue 5 (12th February 2014) - Van Gerven, Nani; Goyal, Parveen; Vandenbussche, Guy; De Kerpel, Maia; Jonckheere, Wim; De Greve, Henri; Remaut, Han
Summary Curli are functional amyloids expressed as fibres on the surface of Enterobacteriaceae. Contrary to the protein misfolding events associated with pathogenic amyloidosis, curli are the result of a dedicated biosynthetic pathway. A specialized transporter in the outer membrane, CsgG, operates in conjunction with the two accessory proteins CsgE and CsgF to secrete curlin subunits to the extracellular surface, where they nucleate into cross‐beta strand fibres. Here we investigate the substrate tolerance of the CsgG transporter and the capability of heterologous sequences to be built into curli fibres. Non‐native polypeptides ranging up to at least 260 residues were exported when fused to the curli subunit CsgA. Secretion efficiency depended on the folding properties of the passenger sequences, with substrates exceeding an approximately 2 nm transverse diameter blocking passage through the transport channel. Secretion of smaller passengers was compatible with prior DsbA‐mediated disulphide bridge formation in the fusion partner, indicating that CsgG is capable of translocating non‐linear polypeptide stretches. Using fusions we further demonstrate the exported or secreted heterologous passenger proteins can attain their native, active fold, establishing curli biogenesis pathway as a platform for the secretion and surface display of small heterologous proteins.